FINANCIAL LITERACY AND PERCEIVED EASE OF QRIS USE IN THE CASHLESS ERA - Indra Yani; Catur Fatchu Ukhriyawati; Rizki Eka Putra (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
The rapid expansion of digital payment systems has accelerated the transition toward a cashless society, with QRIS (Quick Response Code Indonesian Standard) emerging as a key innovation in Indonesia. Despite its widespread availability, adoption levels vary among users, indicating the influence of underlying behavioral and cognitive factors. This study examines the relationship between financial literacy and perceived ease of QRIS use, and how these factors influence behavioral intention to adopt the system. Using a structured survey approach, data were collected from Generation Z users, consumers, and small business actors. The study applies regression and Structural Equation Modeling (SEM) to analyze the relationships among financial literacy, perceived ease of use, and adoption intention. The findings reveal that financial literacy significantly enhances perceived ease of use, which in turn positively influences behavioral intention to use QRIS. Additionally, perceived ease of use acts as a key mediator in this relationship. The study highlights the importance of both user knowledge and system design in promoting digital payment adoption. It contributes to the literature on financial technology and consumer behavior by providing an integrated perspective on digital payment acceptance. The findings suggest that improving financial literacy and system usability can significantly